"Are We Doing Damage?" Choosing an Urban Public School in an Era of Parental Anxiety. (22nd February 2013) - Cucchiara, Maia
<x xml:space="preserve">Abstract</x> There is an ample scholarly and popular literature describing the rise in "anxiety" among middle‐class parents. This paper draws from a study of urban middle‐class parents who were considering sending their children to public school. Focusing on one neighborhood and its school, it describes the impact of anxiety on the choice process. It further examines the emergence of a counter‐movement among parents who saw their choice of the school as rejection of contemporary "helicopter parenting."